THE IMPACT OF DYNAMIC CAPABILITIES BASED ON LEARNING IN INFORMATION TECHNOLOGY AN EXPLORATORY STUDY OF THE OPINIONS OF A GROUP OF EMPLOYEES OF UR STATE COMPANY - Ahmed Azeez Saud; Reyath Thea Azeez; Ali S Habeeb (Scholar Express Journals, 2022)
His study aimed to crystallize a clear vision about the impact of dynamic capabilities in creating business value, and again through information technology that works to strengthen the relationship. My application for the opinions of (330) employees of Ur State Company. The study dealt with dynamic capabilities as an independent variable through (the ability to learn), and information technology as a dependent variable in four dimensions (hardware, equipment, software, databases, and networks). The study relied on the questionnaire as a main tool for collecting data related to its variables. The results showed that there is a significant correlation and effect between dynamic capabilities in its various dimensions, value creation, dynamic capabilities, information technology, information technology and value. Create. The study came out with a set of recommendations, foremost of which is the need to work on creating a clear and common understanding among the employees of the Ur State Company. The topic of the research is related to the strategic direction of their company by involving them in the process of formulating its strategies related to the development of its investments and exploratory activities and enabling it to make decisions that support the orientation of its institutions towards creative businesses.
Keywords: dynamic capabilities; information technology